THE EFFECT OF LIGHT INTENSITY TO GROWTH AND ASTAXATHIN ACCUMULATION OF Haematococcus pluvialis IN PHOTOBIOREACTOR - MUFLIHAH MULYANINGRUM (NIM : 11213041), ISNA
Light is an important factor in growth and it can stimulate the formation of astaxanthin in Haematococcus pluvialis. To determine the effect of high intensity light regulation on the growth and astaxanthin accumulation of H. pluvialis, 36 W fluorescent lamps were used and set the distance with photobioreactor to made high light intensity variation. Variations of light intensity used were 40 (control), 60, 80, 100, 120, and 140 μmol photons m-2 s-1. In this study, we measured the dry weight of the cell, temperature measurement, pH, medium phosphate content, medium nitrate content, chlorophyll content, carotenoid content, and astaxanthin content. The results showed that high light intensity gave significant effect to H. pluvialis growth by giving light intensity of 120 μmol photon m-2 s-1 resulted in the highest rate of specific growth (μ) and the fastest doubling time (dt). While the variation of high light intensity given did not affect the temperature and pH culture. The nitrate and phosphate content of the medium decreased over time in each treatment while the chlorophyll and carotenoid levels increased. The results of astaxanthin analysis test using HPLC with methanol:water = 95:5 (v/v) as mobile phase at wavelength () = 474 nm showed that light with light intensity of 120 μmol photon m-2 s-1 resulted highest astaxanthin content.